Trimethylsilyl group migrations in cryogenic ozonolysis of trimethylsilylethene: evidence for nonconcerted primary ozonide decomposition pathway - Fajgar, R; Roithová, J; Pola, J (The Journal of organic chemistry, 2001)
The identification of trimethylsiloxy-1,2-dioxetane and 2-trimethylsilyloperoxyacetaldehyde and assignment of trimethylsiloxymethyl formate as products of the low-temperature ozonolysis of trimethylsilylethene demonstrate feasibility of migrations of trimethylsilyl group in a dioxygen-centered (oxyperoxy) diradical produced via a homolytic cleavage of each of both O-O bonds in the primary ozonide. The results provide the first experimental evidence on the nonconcerted decomposition of the primary ozonide.